Road structures at urban intersections, bus stops and bus lanes

By adopting a multi-layer combination design in the road structure, including semi-flexible materials sprayed with lime agent, phase change energy storage materials and high-modulus bitumen mixture with high proportion of RAP, combined with bagasse fiber and waste rubber powder, the current solution is solved There are problems of insufficient crack resistance and serious rut ​​diseases in the technology, which improves the durability and anti-slip performance of the road surface, and realizes the recycling of waste.

CN111118999BActive Publication Date: 2025-01-10GUANGXI TRANSPORTATION SCI & TECH GRP CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202010050705.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-01-17
Publication Date
2025-01-10
Estimated Expiration
2040-01-17

AI Technical Summary

Technical Problem

The existing semi-flexible pavement structure has problems such as poor crack resistance, insufficient durability, serious rut ​​diseases, poor anti-slip performance and difficulty in alleviating the urban heat island effect in urban intersections, bus stops and bus lanes.

Method used

The road structure is designed using a surface layer, a middle surface layer, a lower layer, a base layer and a bottom layer. The surface layer is a semi-flexible material sprayed with lithologic agent, the middle surface layer is mixed with phase change energy storage material, and the lower layer is high High-modulus asphalt mixture with proportional RAP, the base layer is mixed with bagasse fiber, waste rubber powder and water-absorbing resin, the base layer is assembled regular hexagonal prism porous cement concrete, and a modified asphalt adhesive layer is provided between each layer to enhance Bonding and waterproofing.

Benefits of technology

It improves the rut resistance, slip resistance and fatigue performance of the road surface, extends the service life of the road surface, alleviates the urban heat island effect, and realizes the reuse of waste, reducing construction costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111118999B_ABST
    Figure CN111118999B_ABST
Patent Text Reader

Abstract

The invention discloses a road structure for a city intersection, a bus station and a bus lane, wherein the road structure includes a surface layer, a middle surface layer, a lower layer, a base layer and a subbase layer from top to bottom, and a rubber asphalt stress absorption layer is arranged between the lower layer and the base layer, the surface layer is composed of a semi-flexible material SFA13 sprayed with a stone-exposing agent of 4cm to 6cm; the middle surface layer is composed of a semi-flexible material SFA16 of 6cm to 8cm mixed with a phase change energy storage material; the lower layer is composed of an 8cm to 10cm EME20 high modulus asphalt mixture, the base layer is composed of 18cm to 20cm C-B-1 cement-stabilized graded crushed stone or gravel mixed with bagasse fiber, waste rubber powder and water-absorbing resin polyacrylic acid sodium salt, and the subbase layer is composed of 15cm to 18cm assembled regular hexagonal porous cement concrete. The present invention improves the water stability, crack resistance and durability of the road structure by integrating and optimizing the pavement paving structure, improves the road surface anti-rutting, anti-skid performance and fatigue performance, alleviates the urban heat island effect to a certain extent, and realizes the reuse of waste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of road engineering, and in particular relates to road structures of urban intersections, bus stops and bus lanes. Background Art

[0002] Road intersections are the main areas for vehicles to start, stop and brake, and vehicles are severely channelized. Under the influence of various factors, traditional asphalt pavements are prone to congestion, rutting, waves and other phenomena. Although bus stops only occupy a small section of the road, as an important part of the normal operation of urban traffic, the lateral force of turning when buses enter or leave the station, the friction resistance when parking, the friction force when starting, etc., the asphalt pavement is very likely to induce rutting diseases. At the same time, bus lanes are fully channelized lanes, which require high high-temperature deformation resistance of pavement materials. Ordinary asphalt pavement structures are prone to early diseases such as rutting and cracking. For this reason, how to improve the high-temperature rutting resistance of asphalt pavements and extend the service life of pavements has become a research focus for road workers.

[0003] The publication number is CN206503047U, and the disclosed bus-only road pavement structure involves a wear layer, a high modulus anti-rutting deformation layer, an anti-fatigue layer, and a semi-flexible anti-cracking layer. The announcement number is CN206529665U, and the disclosed urban bus-only road composite pavement structure includes a flexible pavement material upper layer, a high modulus asphalt concrete middle layer, a continuous reinforced concrete lower layer, and a cement-stabilized crushed stone semi-rigid base layer. The publication number is CN105481322A, and a semi-flexible composite pavement structure and a preparation method thereof are disclosed, wherein the semi-flexible composite pavement structure is composed of 70-80% of a macroporous asphalt mixture matrix and 20-30% of rubber powder cement mortar. The publication number is CN101096837A, and a construction method of a semi-flexible composite pavement is disclosed, including first preparing a macroporous matrix asphalt mixture, and then pouring cement mortar with cement as the main component into the macroporous matrix asphalt mixture, and performing surface treatment and maintenance for a certain period of time after paving. Publication number CN106587842A discloses a method for preparing cement grouting materials in the raw materials of semi-flexible pavement materials. Publication number CN208415027U discloses a semi-flexible composite pavement structure, the upper layer is a coating layer, and the lower layer is a composite layer of cement mixed mortar and asphalt material. Publication number CN205134126U discloses a semi-flexible asphalt pavement base structure, including an upper base and a lower base, the lower base is a fly ash stabilized gravel layer, and the upper base is a foamed asphalt in-situ cold recycled fly ash gravel layer. Publication number CN205134128U discloses a semi-flexible asphalt pavement structure, including an SMA-13, Sup-13 or AC-13 upper layer and a cement-emulsified asphalt cold recycled asphalt mixture lower layer. The publication number is CN103866667A, and the disclosed semi-flexible heavy-duty road pavement structure includes: the surface layer is a high-viscosity modified asphalt mixture, the middle surface layer is a high-modulus asphalt mixture, the lower layer is a low-grade road asphalt dense-graded asphalt stabilized macadam, and the semi-flexible base layer is a skeleton-compacted cement-emulsified asphalt concrete. The above-mentioned semi-flexible pavement structure mainly includes two types, one is a cement-based grouting material that fills large voids with an open-graded asphalt mixture, and the other is cement-emulsified asphalt concrete. Since the components of cement-emulsified asphalt concrete are cement, aggregate and emulsified asphalt, there are compatibility and compatibility issues between the raw materials. At the same time, cement-emulsified concrete has low compressive strength, poor water stability, low viscosity strength, and seriously insufficient durability, making it difficult to be competent for the surface layer of the road. At present, there are very few publicly reported application projects of cement-emulsified asphalt concrete. To this end, the domestic and international road fields have reached a consensus on the definition of semi-flexible materials (pavement), that is, a composite material (pavement) formed by pouring cement-based grouting materials with special properties into an open-graded skeleton void structure asphalt mixture.

[0004] Due to the poor crack resistance and insufficient durability of cement-stabilized graded crushed stone or gravel, it is easy to cause problems such as cracking of the base layer and reflective cracks in the pavement, which is a stubborn problem of the current semi-rigid base layer and has been troubling road engineering personnel. In view of the rutting disease on special sections of urban roads, the current pavement structure scheme with semi-flexible pavement as the surface layer has achieved certain results. However, due to the performance and construction process of cement-based grouting materials, the structural depth of the surface layer of the semi-flexible pavement is small, the anti-skid performance is poor, and some grouting materials attached to the aggregate surface are easy to fall off after hardening. At the same time, how to alleviate the urban heat island effect and realize the recycling of waste is one of the keys to the sustainable development of transportation infrastructure construction in today's era. Summary of the invention

[0005] The purpose of the present invention is to provide a road structure for urban intersections, bus stops and bus lanes. The present invention improves the water stability, crack resistance and durability of the base layer by improving the material composition design of each layer of the road surface, integrating and optimizing the pavement pavement structure design, avoiding scouring damage, shrinkage cracking and reflective cracks of the base layer, improving the road surface's rutting resistance, skid resistance and fatigue performance, alleviating the urban heat island effect to a certain extent, achieving the reuse of waste, and reducing the thickness of the road surface, reducing the cost of the full life cycle project. In order to achieve the above purpose, the present invention adopts the following technical effects:

[0006] According to one aspect of the present invention, a road structure for urban intersections, bus stops and bus lanes is provided, wherein the road structure comprises, from top to bottom, a surface layer, a middle layer, a lower layer, a base layer and a subbase layer, wherein a rubber asphalt stress absorption layer is arranged between the lower layer and the base layer, wherein the surface layer is composed of a 4cm~6cm layer of a semi-flexible material SFA13 sprayed with a stone-exposing agent; the middle layer is composed of a 6cm~8cm layer of a semi-flexible material SFA16 mixed with a phase change energy storage material; the lower layer is composed of an 8cm~10cm layer of an EME20 high modulus asphalt mixture with a high proportion of RAP, the base layer is composed of an 18cm~20cm layer of CB-1 cement-stabilized graded crushed stone or gravel mixed with bagasse fiber, waste rubber powder and water-absorbing resin sodium polyacrylate, and the subbase layer is composed of a 15cm~18cm assembled regular hexagonal porous cement concrete layer.

[0007] The above scheme is further preferred, wherein a first adhesive layer is provided between the surface layer and the middle surface layer, and a second adhesive layer is provided between the middle surface layer and the lower layer, and the first adhesive layer and the second adhesive layer are SBS modified asphalt adhesive layers or modified emulsified asphalt adhesive layers, and the spreading amount per unit area is 0.7-0.8 kg / m 2 .

[0008] Preferably, the thickness of the rubber asphalt stress absorption layer is 0.8cm~1.3cm; the absorption layer can inhibit the development of reflective cracks between the underlying layer and the base layer, prevent moisture from invading the pavement structure layers, and play a role in waterproofing damage. At the same time, the rubber asphalt has super strong viscosity, strengthens the interlayer bonding, and is beneficial to the stress of the pavement structure.

[0009] The above scheme is further preferred in that a gap is provided along the bottom direction at the lower half of the base layer, the distance between adjacent gaps is 0.6m-1.5m, and the width of the gap is 0.5cm-2.5cm.

[0010] The above scheme is further preferred, that the semi-flexible material SFA13 is prepared by pouring cement grouting material into a rubber asphalt mixture, wherein the void ratio of the rubber asphalt mixture is 20%~28%, and the rubber asphalt mixture is mixed, spread and compacted by the following raw materials in the following weight ratio: aggregate: mineral powder: rubber asphalt = 100:3~5:3.5~5.5; the cement grouting material is prepared by the following raw materials in weight parts: 30~50 parts of ordinary Portland cement, 5~10 parts of grade II fly ash, 10~15 parts of fine sand, 0.5~2 parts of sulfate-based early strength agent, 0.1~0.3 parts of polycarboxylic acid water reducer, 1~6 parts of saponin air entraining agent, 1~4 parts of carboxylated styrene butadiene latex, 0.1~0.4 parts of calcium carbonate, and 15~35 parts of water.

[0011] The above scheme is further preferred, that the semi-flexible material SFA16 of the phase change energy storage material is prepared by pouring cement grouting material containing phase change energy storage material into a rubber asphalt mixture, the void ratio of the rubber asphalt mixture is 20%~28%, and the rubber asphalt mixture is mixed, spread and compacted by the following raw materials and weight ratio, aggregate: mineral powder: rubber asphalt = 100:3~5:3.5~5.5; the cement grouting material of the phase change energy storage material is prepared by the following raw materials in parts by weight: 30~50 parts of ordinary Portland cement, 5~10 parts of grade II fly ash, 5~10 parts of fine sand, 0.5~2 parts of sulfate early strength agent, 0.1~0.3 parts of polycarboxylic acid water reducer, 1~6 parts of sodium carbonate, 0.1~0.4 parts of calcium carbonate, 12~32 parts of water, and 3~5 parts of phase change energy storage material.

[0012] The above scheme is further preferred, in which emulsified asphalt is wrapped on the outside of the semi-flexible material SFA16 of the phase change energy storage material, and the semi-flexible material SFA16 of the phase change energy storage material is prepared by using expanded graphite as an energy storage carrier and one or more of paraffin, fatty acid, and polyethylene glycol as phase change materials, and the mass ratio of the phase change material to the energy storage carrier is 40%-80%.

[0013] The above scheme is further preferred, that the EME20 high modulus asphalt mixture with a high proportion of RAP is formed by mixing, paving and compacting raw materials in the following weight ratio: aggregate: mineral powder: low-grade road asphalt = 100: 5~6: 5.5~6.5, wherein the aggregate contains 25~50% of RAP old materials.

[0014] The above scheme is further preferred, wherein the base layer is formed by mixing, spreading and compacting CB-1 cement-stabilized graded crushed stone or gravel of bagasse fiber, waste rubber powder and water-absorbent resin sodium polyacrylate, and the base layer is formed by mixing, spreading and compacting the following raw materials in the following weight ratio: aggregate: ordinary Portland cement: bagasse fiber: waste rubber powder: water-absorbent resin sodium polyacrylate = 100: 4~6.5: 0.3~0.8: 0.5~3.5: 0.1~0.3.

[0015] The above scheme is further preferred, the strength grade of the 15~18cm assembled regular hexagonal porous cement concrete should not be less than C20, the porosity is 10%~15%, and the assembled regular hexagonal porous cement concrete is composed of the following raw materials: 5mm~10mm coarse aggregate 1629kg / m 3 , cement 503 kg / m 3 , water 150.9 kg / m 3 , water reducing agent 2.0kg / m 3 、Rubber powder 15.1kg / m 3 and polyvinyl alcohol powder 4.0kg / m 3 ; Wherein, the coarse aggregate is made of natural coarse aggregate 814.5~1140.3kg / m 3 and recycled coarse aggregate 488.7~814.5 kg / m 3 composition.

[0016] According to another aspect of the present invention, a construction method for a road structure of an urban intersection, a bus station, and a bus lane is provided. The construction method for the road structure is performed according to the following steps:

[0017] 1) Determination of mineral aggregate gradation: mainly for aggregate gradation. The new aggregate of high modulus asphalt mixture EME20 is a combination of basalt and limestone;

[0018] 2) Preparation of auxiliary materials: ① Preparation of phase change energy storage material, wherein the phase change energy storage material uses expanded graphite as the energy storage carrier, and uses one or more of paraffin, fatty acid, polyethylene glycol, etc. as the phase change material, and the outside of the phase change energy storage material is wrapped with emulsified asphalt to further ensure that there is no liquid leakage during the phase change process; the preparation process of the energy storage carrier is as follows: first, weigh 100g of expanded graphite, 400g of polyethylene glycol and 800g-1200g of emulsified asphalt for standby use, place the expanded graphite in a 70℃~80℃ oven, and heat for 10h~12h to ensure that there is no moisture in the expanded graphite; secondly, dissolve polyethylene glycol in distilled water at 50℃~60℃ to prepare a polyethylene glycol aqueous solution; thirdly, mix the dried expanded graphite with the polyethylene glycol aqueous solution, and ultrasonically oscillate at 60℃ for 0.5h; then place the expanded graphite and polyethylene glycol mixed solution in a vacuum drying oven at 80℃ and evacuate for 4h ~5h, so that the pores of the expanded graphite are filled with polyethylene glycol, thereby obtaining an expanded graphite-polyethylene glycol composite material; finally, slowly adding the expanded graphite-polyethylene glycol composite material to the emulsified asphalt, stirring synchronously and controlling the stirring speed from slow to fast, and when all of them are added, rotating at a constant speed for 0.5h, with a stirring speed of 1000-1500 rpm, so that the emulsified asphalt can fully wrap the composite material, thereby preparing a polyethylene glycol phase change energy storage material;

[0019] ② Preparation of cement grouting material, proportioning according to the weight of each raw material in the cement grouting material;

[0020] ③ Preparation of phase change energy storage cement grouting material. The preparation process is as follows: first, phase change energy storage material, ordinary Portland cement, fly ash and fine sand are mixed together for 3 minutes, and then sulfate early strength agent, polycarboxylate water reducer, saponin air entraining agent, carboxyl styrene butadiene latex, calcium carbonate and water are added, and then mixed and stirred for 5 minutes to ensure that the phase change energy storage material can be more evenly dispersed in the cement grouting material.

[0021] 3) Pavement structure construction: from bottom to top, carry out the prefabricated hexagonal porous cement concrete subbase, cement stabilized gravel base, rubber asphalt stress absorption layer, lower layer, bonding layer, middle surface layer and surface layer.

[0022] In summary, since the present invention adopts the above technical solution, the present invention has the following technical effects:

[0023] (1) The present invention mainly adopts semi-flexible pavement, cement concrete pavement and asphalt pavement to form a composite pavement structure. The surface of the semi-flexible material is exposed to stones by using a stone-exposing agent, thereby solving the problems of uneven slurry scraping and poor anti-skid performance of traditional semi-flexible pavements, improving the anti-rutting performance of asphalt pavements, and using the prepared composite phase change material to mix with the semi-flexible material. When the temperature is high, the road surface temperature can be reduced to alleviate the urban heat island effect. When the temperature is low, the road surface temperature can be increased to alleviate the impact of freezing on road driving safety.

[0024] (2) The present invention adds bagasse fiber, waste rubber powder and high molecular water-absorbing resin to cement-stabilized crushed stone, which can not only improve the water stability, crack resistance and durability of the base layer, reduce or avoid shrinkage cracking of the base layer and reflective cracks on the road surface, but also reuse waste, save natural resources, and achieve sustainable development of transportation infrastructure construction;

[0025] (3) The present invention adopts assembled regular hexagonal porous cement concrete with recycled coarse aggregate from waste cement concrete as one of the main raw materials, thus realizing the large-scale utilization of waste and greatly improving the construction efficiency of urban road construction. The regular hexagonal porous cement concrete prefabricated board can strengthen the transfer of load and solve the problem of water damage under the base. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the structure of the road structure of the city intersection, bus station and bus lane of the present invention;

[0027] Figure 2 It is a top view of the assembled regular hexagonal porous cement concrete;

[0028] Figure 3 It is a top view of the assembled regular hexagonal porous cement concrete;

[0029] In the accompanying drawings, there are surface layer 1, first adhesive layer 2, middle surface layer 3, second adhesive layer 4, lower layer 5, rubber asphalt stress absorbing layer 6, base layer 7, subbase layer 8, and gap 9. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and preferred embodiments. However, it should be noted that many details listed in the specification are only for the purpose of enabling the reader to have a thorough understanding of one or more aspects of the present invention, and these aspects of the present invention can be implemented even without these specific details.

[0031] Embodiment 1, as Figure 1As shown, according to a road structure of a city intersection, a bus station and a bus lane of the present invention, the road structure comprises, from top to bottom, a surface layer 1, a middle surface layer 3, a lower layer 5, a base layer 7 and a subbase layer 8, and a rubber asphalt stress absorption layer 6 is arranged between the lower layer 4 and the base layer 7, wherein the surface layer 1 is composed of a 4cm~6cm semi-flexible material SFA13 sprayed with a stone exposure agent; the middle surface layer 3 is composed of a 6cm~8cm semi-flexible material SFA16 doped with a phase change energy storage material; the lower layer 5 is composed of an 8cm~1 The base layer 7 is composed of 18-20 cm thick CB-1 cement stabilized graded crushed stone or gravel mixed with bagasse fiber, waste rubber powder and water-absorbing resin polyacrylic acid sodium salt. A first adhesive layer 2 is arranged between the surface layer 1 and the middle surface layer 3, and a second adhesive layer 4 is arranged between the middle surface layer 3 and the lower layer 5. The first adhesive layer 2 and the second adhesive layer 4 are SBS modified asphalt adhesive layers or modified emulsified asphalt adhesive layers, and the spreading amount per unit area is 0.7-0.8 kg / m 2 , the thickness of the rubber asphalt stress absorbing layer 6 is 0.8 cm ~ 1.3 cm;

[0032] In the present invention, since cement stabilized graded crushed stone or gravel has poor crack resistance and insufficient durability, it is easy to cause problems such as base cracking and road surface reflection cracks, and water accumulation in the base induces base scouring and damage, and the durability is insufficient. For rutting diseases in special sections of urban roads, a subbase 8 is set below the base 7, such as Figure 1 , Figure 2 and Figure 3 As shown, the base layer 8 is composed of 15cm~18cm assembled regular hexagonal porous cement concrete; a gap 9 is arranged along the bottom direction in the lower half of the base layer 8, the distance between adjacent gaps 9 is 1m (that is, gaps 9 are arranged between adjacent regular hexagonal porous cement concretes), and the width of the gap 9 is 1cm-1.5cm, so that excess water in the assembled porous cement concrete 5 can penetrate into the drainage ditch or other auxiliary drainage equipment along the gap 50.

[0033] In the present invention, the semi-flexible material SFA13 is prepared by pouring cement grouting material into a rubber asphalt mixture, wherein the void ratio of the rubber asphalt mixture is 20%~28%, and the rubber asphalt mixture is mixed, spread and compacted by the following raw materials in the following weight ratio: aggregate: mineral powder: rubber asphalt = 100: 3~5: 3.5~5.5; the cement grouting material is prepared by the following raw materials in parts by weight: 30~50 parts of ordinary Portland cement, 5~10 parts of grade II fly ash, 10~15 parts of fine sand, 0.5~2 parts of sulfate early strength agent, 0.1~0.3 parts of polycarboxylic acid water reducer, 1~6 parts of saponin air entraining agent, 1~4 parts of carboxylated styrene butadiene latex, 0.1~0.4 parts of calcium carbonate, and 15~35 parts of water.

[0034] The semi-flexible material SFA16 of the phase change energy storage material is prepared by pouring cement grouting material containing phase change energy storage material into rubber asphalt mixture. The design target void ratio of the rubber asphalt mixture is 20%~28%. The rubber asphalt mixture is mixed, spread and compacted by the following raw materials and weight ratios: aggregate: mineral powder: rubber asphalt = 100: 3~5: 3.5~5.5; the cement grouting material of the phase change energy storage material is prepared by the following raw materials in parts by weight: 30~50 parts of ordinary Portland cement, 5~10 parts of grade II fly ash, 5~10 parts of fine sand, 0.5~2 parts of sulfate early strength agent, 0.1~0.3 parts of polycarboxylate water reducer, 1~6 parts of sodium carbonate, 0.1~0.4 parts of calcium carbonate, 12~32 parts of water, and 3~5 parts of phase change energy storage material;

[0035] Emulsified asphalt is wrapped outside the phase change energy storage material. The phase change energy storage material is prepared by using expanded graphite as an energy storage carrier and one or more of paraffin, fatty acid, and polyethylene glycol as phase change materials. The mass ratio of the phase change material to the energy storage carrier is 40%-80%.

[0036] The EME20 high modulus asphalt mixture with a high proportion of RAP is prepared by mixing, paving and compacting raw materials in the following weight ratio: aggregate: mineral powder: low-grade road asphalt = 100: 5~6: 5.5~6.5, wherein the aggregate contains 25~50% of RAP old materials.

[0037] The base layer 7 is formed by mixing, spreading and compacting CB-1 cement-stabilized crushed stone or gravel with bagasse fiber, waste rubber powder and water-absorbent resin sodium polyacrylate. The base layer 7 is formed by mixing, spreading and compacting the following raw materials in the following weight ratio: aggregate: ordinary Portland cement: bagasse fiber: waste rubber powder: water-absorbent resin sodium polyacrylate = 100: 4~6.5: 0.3~0.8: 0.5~3.5: 0.1~0.3.

[0038] The strength grade of the 15-18 cm assembled regular hexagonal porous cement concrete should not be less than C20, and the porosity is 10%-15%. The assembled regular hexagonal porous cement concrete is composed of the following raw materials: 5 mm-10 mm coarse aggregate 1629 kg / m 3 , cement 503 kg / m 3 , water 150.9 kg / m 3 , water reducing agent 2.0kg / m 3 、Rubber powder 15.1kg / m 3 and polyvinyl alcohol powder 4.0kg / m 3 ; Wherein, the coarse aggregate is made of natural coarse aggregate 814.5~1140.3kg / m 3and recycled coarse aggregate 488.7~814.5kg / m 3 Composition. The present invention uses old cement concrete waste as the raw material of coarse aggregate for assembled regular hexagonal porous cement concrete, which not only improves the level of resource reuse and recycling, but also speeds up the construction progress, strengthens the control of project quality, and avoids water damage caused by water accumulation at the base, prolongs the service life of roads, and realizes the sustainable development of transportation infrastructure construction. In general, the pavement paving structure belongs to a new type of long-life pavement structure with excellent road performance and good durability. It is an effective technical means to solve pavement rutting diseases, and reduces the thickness of the pavement, reducing the cost of the entire life cycle project, and conforms to the requirements of the times of "people-oriented, energy conservation and emission reduction, resource recycling, and environmental protection."

[0039] In the present invention, the aggregate is basalt or limestone or granite. For granite aggregate, a stripping agent must be used to improve the adhesion between asphalt and aggregate. The mineral powder is limestone powder, and the properties of the aggregate and the mineral powder must meet the corresponding technical requirements of the current "Technical Specifications for Highway Asphalt Pavement Construction" (JTG F40-2004). The specific requirements are as follows: the mineral aggregate mix ratios of the different structural layers correspond to the following sieve hole sizes: 26.5, 19, 16, 13.2, 9.5, 4.75, 2.36, 1.18, 0.6, 0.3, 0.15, 0.075 mm; for the semi-flexible material SFA13, the weight percentage pass rates are: 100, 100, 100, respectively. , 90~100, 50~80, 12~30, 10~22, 6~18, 4~15, 3~12, 3~8, 2~6; for the semi-flexible material SFA16, the weight percentage pass rates are: 100, 100, 90~100, 70~90, 45~70, 12~30, 10~22, 6~18, 4~15, 3~12, 3~8, 2~6; for high modulus For asphalt mixture EME20, the weight percentage passing rates are: 100, 90~100, 80~95, 70~85, 60~75, 40~55, 30~40, 20~30, 15~20, 10~16, 6~10, 4~8; for cement stabilized graded crushed stone or gravel CB-1, the weight percentage passing rates are: 100, 82~86, 73~79, 65~72, 53~62, 35~45, 22~31, 13~22, 8~15, 5~10, 3~7, 2~5; the aggregate is basalt or limestone or granite, and for granite aggregate, a stripping agent must be taken to improve the adhesion between asphalt and aggregate. The mineral powder is limestone powder, and the properties of the aggregate and the mineral powder must meet the requirements of the current specifications. The gradation range of the mineral material of the pavement structure is shown in Table 1.

[0040] Table 1: Mass percentage of ore passing through each sieve hole (mm)

[0041]

[0042] According to another aspect of the present invention, a construction method for a road structure of an urban intersection, a bus station, and a bus lane is provided. The construction method for the road structure is performed according to the following steps:

[0043] 1) Determination of mineral aggregate gradation: The new aggregate of high modulus asphalt mixture EME20 is a combination of basalt and limestone, the filler is limestone powder, and the old material comes from the middle surface layer of the asphalt pavement. The gradation after trichloroethylene extraction is shown in Table 2, where the old material content is 30% and the mass fraction of asphalt in the old material is 4.6%.

[0044] Table 2: Mass percentage of RAP waste material passing through each sieve hole (mm)

[0045]

[0046] The grading of other mixtures is shown in Table 3. The aggregate is limestone or basalt, and the filler is limestone powder. Their properties meet the requirements of my country's standards.

[0047] Table 3: Mass percentage of ore passing through each sieve hole (mm)

[0048]

[0049] The EME20 high modulus asphalt mixture with a high proportion of RAP (25% to 50%) is formed by mixing, paving and compacting raw materials in the following weight ratio: aggregate: mineral powder: low-grade road asphalt = 100: 5~6: 5.5~6.5, wherein the aggregate contains 25%~50% of RAP old materials. The base layer 6 is formed by mixing, paving and compacting CB-1 cement-stabilized graded crushed stone or gravel of bagasse fiber, waste rubber powder and water-absorbing resin polyacrylic acid sodium salt. The base layer 6 is formed by mixing, paving and compacting raw materials in the following weight ratio: aggregate: ordinary silicate cement: bagasse fiber: waste rubber powder: water-absorbing resin polyacrylic acid sodium salt = 100: 4~6.5: 0.3~0.8: 0.5~3.5: 0.1~0.3.

[0050] 2) Preparation of auxiliary materials:

[0051] ① Preparation of phase change energy storage materials

[0052] The phase change energy storage material expanded graphite is an energy storage carrier, and one or more of paraffin, fatty acid, polyethylene glycol, etc. are used as phase change materials. The mass ratio of phase change material to energy storage carrier is 40%~80%, and the emulsified asphalt is wrapped outside to further ensure that there is no liquid leakage during the phase change process; the type of phase change material is determined according to the climatic conditions and temperature control goals of the road. Taking the roads in Guangxi as an example, the summer temperature in this area is high, the heat is abundant, and the road surface disease rutting is more prominent. Therefore, the phase change temperature obtained by combining one or more phase change materials is preferably 30℃~50℃. Polyethylene glycol is selected as the phase change material. The preparation process of the energy storage carrier (phase change energy storage) material is as follows: first, weigh 100g of expanded graphite, 400g of polyethylene glycol and 800g-1200g of emulsified asphalt for standby use, place the expanded graphite in a 70℃~80℃ oven, and heat it for 10h~12h to ensure expansion. There is no water in the graphite; secondly, polyethylene glycol is dissolved in distilled water at 50°C~60°C to prepare a polyethylene glycol aqueous solution; thirdly, the dried expanded graphite is mixed with the polyethylene glycol aqueous solution and ultrasonically oscillated at 60°C for 0.5h; the expanded graphite and polyethylene glycol mixed solution is placed in a vacuum drying oven at 80°C and evacuated for 4.5h to fill the pores of the expanded graphite with polyethylene glycol, thereby obtaining an expanded graphite-polyethylene glycol composite material; finally, the expanded graphite-polyethylene glycol composite material is slowly added to the emulsified asphalt, stirred simultaneously and the stirring speed is controlled from slow to fast. After all of it is added, it is rotated at a constant speed for 0.5h and the stirring speed is 1200 rpm so that the emulsified asphalt can fully wrap the composite material, thereby preparing a polyethylene glycol phase change energy storage material, and the total mass fraction of the emulsified asphalt and the polyethylene glycol phase change energy storage material is 80% (accounting for 80% of the total mass).

[0053] ② Preparation of cement grouting material

[0054] According to the weight ratio of each raw material in the cement grouting material, 42% ordinary Portland cement, 9% grade II fly ash, and 12% fine sand are mixed and stirred for 2 minutes, and then 1% sulfate early strength agent, 0.2% polycarboxylate water reducer, 2.5% saponin air entraining agent, 3% carboxylated styrene butadiene latex, 0.3% calcium carbonate, and 30% water are added and mixed and stirred for 3 minutes to make the mixture uniform to complete the preparation of the cement grouting material.

[0055] ③ Preparation of phase change energy storage cement grouting material

[0056] A certain mass of phase change energy storage material is prepared according to the above method. Taking into account the adverse effects of high dosage of phase change energy storage material on the mechanical strength and durability of the mixture, as well as the compatibility of phase change energy storage material with cement grouting material, the phase change energy storage cement grouting material needs to be prepared according to the following method: first, 3% phase change energy storage material, 42% ordinary Portland cement, 9% fly ash, and 12% fine sand are mixed together and stirred for 3 minutes, and then 1% sulfate early strength agent, 0.2% polycarboxylate water reducer, 2.5% saponin air entraining agent, 3% carboxylated styrene butadiene latex, 0.3% calcium carbonate, and 30% water are added. After mixing, stir for 5 minutes to ensure that the phase change energy storage material can be more evenly dispersed in the cement grouting material.

[0057] 3) Road pavement structure construction

[0058] ① Assembled regular hexagonal porous cement concrete subbase: Assembled regular hexagonal porous cement concrete is composed of the following raw materials: 5mm~10mm coarse aggregate 1629kg / m 3 , cement 503 kg / m 3 , water 150.9 kg / m 3 , water reducing agent 2.0kg / m 3 、Rubber powder 15.1kg / m 3 and polyvinyl alcohol powder 4.0kg / m 3 ; Wherein, the coarse aggregate is made of natural coarse aggregate 814.5~1140.3kg / m 3 and recycled coarse aggregate 488.7~814.5 kg / m 3 The composition is mixed according to the above ratio, cured and transported to the construction site. The flatness of the regular hexagonal porous cement concrete construction needs to be well controlled, and the joints of the assembled panels are filled with cement mortar to provide a good working surface for the base construction.

[0059] ② Cement stabilized gravel base paving: According to the grading of cement stabilized graded gravel mineral materials, aggregate, ordinary Portland cement, bagasse fiber, waste rubber powder, high molecular weight water-absorbing resin polyacrylic acid sodium salt are mixed, spread and rolled in a weight ratio of 100:5:0.6:2.53:0.2 to form a cement stabilized graded gravel base 7, wherein the ordinary Portland cement is PO 42.5, and the basic properties of bagasse fiber and waste rubber powder particles meet the requirements of my country's standards. The present invention adds bagasse fiber, waste rubber powder and high molecular weight water-absorbing resin to cement stabilized gravel, which can not only improve the water stability, crack resistance and durability of the base, but also reduce or avoid shrinkage cracking of the base and reflective cracks on the road surface.

[0060] ③Spreading of stress absorption layer: The binder of stress absorption layer is rubber asphalt, and the aggregate should be hard, clean and cubic crushed stone particles. The basic properties of rubber asphalt and aggregate meet the requirements of my country's standards. The spreading amount of rubber asphalt is 2.5kg / m2. After spreading rubber asphalt, spreading and rolling crushed stone, the paving of stress absorption layer 6 is completed, and its thickness is 10mm.

[0061] ④ Paving of the lower layer: On the stress absorption layer 6, low-grade road asphalt (basic properties as shown in Table 4) and EME20 grading type are used to pave high modulus asphalt mixture technical indicators that meet the requirements of Table 5 to form the lower layer 5. The mass ratio of various materials in the lower layer 5 is aggregate: mineral powder: low-grade road asphalt = 100:5:6.2, and the mass ratio of aggregate including RAP old material and new aggregate is 30:70.

[0062] Table 4: Technical indicators of low-grade road asphalt

[0063]

[0064] Table 5: Technical indicators and requirements of high modulus asphalt mixture

[0065]

[0066] ⑤ Paving of bonding layer and middle surface layer: To ensure the integrity of the pavement structure, a first bonding layer 2 is provided between the surface layer 1 and the middle surface layer 3, and a second bonding layer 4 is provided between the middle surface layer 3 and the lower layer 5. The first bonding layer 2 and the second bonding layer 20 are SBS modified asphalt bonding layers or modified emulsified asphalt bonding layers, and the spreading amount per unit area is 0.7-0.8 kg / m 2 The spreading amount per unit area is 0.73kg / m 2 On the second adhesive layer 4, rubber asphalt and SFA16 grading are used to form an asphalt mixture with a void ratio of 25%, and cement grouting material containing phase change energy storage material is poured into the voids to form the middle surface layer 3, wherein the raw materials of the large void asphalt mixture of the middle surface layer 3 are composed of aggregate: mineral powder: rubber asphalt, and the mass ratio of the various materials is aggregate: mineral powder: rubber asphalt = 100: 3.7: 4.2, wherein the properties of the rubber asphalt are shown in Table 6.

[0067] Table 6: Technical indicators of rubber asphalt

[0068]

[0069] Surface paving: On the first adhesive layer 2, rubber asphalt (basic properties as shown in Table 6) and SFA13 grading are used to form an asphalt mixture with a void ratio of 25%. After cement grouting is poured into the voids, the stone-exposing agent is sprayed to form the surface layer 1. Among them, the surface layer 1 is composed of 4cm~6cm semi-flexible material SFA13 sprayed with stone-exposing agent. The large-void asphalt mixture of the surface layer 1 is composed of aggregate, mineral powder, and rubber asphalt. The mass ratio of each raw material is 100:4.0:4.4. The specific stone-exposing process is as follows: after the cement grouting is poured, the slurry is scraped. When the water film on the road surface disappears, the stone-exposing agent is evenly sprayed. The spraying amount is 150g / m 2 The stone-exposing agent is sprayed twice, with 68% of the amount of the stone-exposing agent sprayed for the first time and 32% of the amount of the stone-exposing agent sprayed for the second time, and the time interval between the two sprayings is 5 minutes. After the spraying is completed, the road surface is covered with a plastic film for curing; a sharp object is used to scratch the road surface. The mark is very shallow but clearly visible and the edge is basically undamaged, which is the appropriate brushing time. At this time, the excess cement slurry on the road surface is washed off, and then the film is covered for the second curing for 4 hours; after the road structure of the present invention is paved, the technical indicators of the pavement after paving are tested and detected as required, and the lateral force coefficient SFC 60 is 67, the structural depth TD is 0.65mm, and the permeability coefficient (ml / min): impermeable; the temperature reduction of the pavement surface layer is 2°C to 5°C. The present invention uses a stone-exposing agent to expose the surface of the semi-flexible material through the above-mentioned scheme, thereby solving the problems of uneven slurry scraping and poor anti-skid performance of traditional semi-flexible pavements; the phase change energy storage material is added to the semi-flexible material, which can reduce the road surface temperature at high temperatures and alleviate the urban heat island effect, and can increase the road surface temperature at low temperatures and alleviate the impact of freezing on road driving safety.

[0070] In Example 2, the surface layer 1 is composed of 4 cm of semi-flexible material SFA13 sprayed with a stone-exposing agent; the middle surface layer 3 is composed of 6 cm of semi-flexible material SFA16 mixed with phase change energy storage material; the lower layer 5 is composed of 10 cm of EME20 high modulus asphalt mixture with a high proportion of RAP, and the base layer 7 is composed of 18 cm of CB-1 cement-stabilized graded crushed stone or gravel mixed with bagasse fiber, waste rubber powder and water-absorbing resin polyacrylic acid sodium salt. A first adhesive layer 2 is arranged between the surface layer 1 and the middle surface layer 3, and a second adhesive layer 4 is arranged between the middle surface layer 3 and the lower layer 5. The first adhesive layer 2 and the second adhesive layer 4 are SBS modified asphalt adhesive layers or modified emulsified asphalt adhesive layers, and the spreading amount per unit area is 0.8 kg / m 2 The thickness of the rubber asphalt stress absorption layer 6 is 0.8 cm; the base layer 8 is composed of 15 cm assembled regular hexagonal porous cement concrete; a gap 9 is provided along the bottom direction in the lower half of the base layer 8, the distance between adjacent gaps 9 is 0.6 m, and the width of the gap 9 is 0.5 cm.

[0071] In an embodiment of the invention, the semi-flexible material SFA13 is prepared by pouring cement grouting into a rubber asphalt mixture, wherein the void ratio of the rubber asphalt mixture is 20%, and the rubber asphalt mixture is mixed, spread and compacted by the following raw materials in the following weight ratio: aggregate: mineral powder: rubber asphalt = 100:3:3.5; the cement grouting material is prepared by the following raw materials in parts by weight: 50 parts of ordinary Portland cement, 5 parts of grade II fly ash, 10 parts of fine sand, 0.5 parts of sulfate-based early strength agent, 0.1 parts of polycarboxylic acid water reducer, 1 part of saponin air entraining agent, 1 part of carboxylated styrene butadiene latex, 0.1 parts of calcium carbonate, and 15 parts of water. The semi-flexible material SFA16 of the phase change energy storage material is prepared by pouring cement grouting material containing phase change energy storage material into rubber asphalt mixture. The design target void ratio of the rubber asphalt mixture is 20%. The rubber asphalt mixture is mixed, spread and compacted by the following raw materials and weight ratio, aggregate: mineral powder: rubber asphalt = 100:3:3.5; the cement grouting material of the phase change energy storage material is prepared by the following raw materials in parts by weight: 30 parts of ordinary Portland cement, 5 parts of grade II fly ash, 5 parts of fine sand, 0.5 parts of sulfate early strength agent, 0.1 parts of polycarboxylic acid water reducer, 1 part of sodium carbonate, 0.1 parts of calcium carbonate, 12 parts of water, and 3 parts of phase change energy storage material; emulsified asphalt is wrapped on the outside of the phase change energy storage material, and the phase change energy storage material is prepared by using expanded graphite as an energy storage carrier and one or more of paraffin, fatty acid, and polyethylene glycol as phase change materials, and the mass ratio of the phase change material to the energy storage carrier is 40%. The preparation process of the energy storage carrier (phase change energy storage) material is as follows: placing expanded graphite in a 70°C oven and heating it for 12 hours to ensure that there is no moisture in the expanded graphite; secondly, dissolving polyethylene glycol in 50°C distilled water to prepare a polyethylene glycol aqueous solution; thirdly, mixing the dried expanded graphite with the polyethylene glycol aqueous solution and ultrasonically oscillating at 60°C for 20 minutes; then placing the expanded graphite and polyethylene glycol mixed solution in an 80°C vacuum drying oven and evacuating it for 4 hours so that the pores of the expanded graphite are filled with polyethylene glycol, thereby obtaining an expanded graphite-polyethylene glycol composite material; finally, slowly adding the expanded graphite-polyethylene glycol composite material to the emulsified asphalt, stirring synchronously and controlling the stirring speed from slow to fast, and when all of them are added, rotating at a constant speed for 0.5 hours at a stirring speed of 1000 rpm so that the emulsified asphalt can fully wrap the composite material, thereby preparing a polyethylene glycol phase change energy storage material, and the total mass fraction of the emulsified asphalt and the polyethylene glycol phase change energy storage material is 80%.

[0072] In Example 3, the surface layer 1 is composed of 6 cm of semi-flexible material SFA13 sprayed with a stone-exposing agent; the middle surface layer 3 is composed of 8 cm of semi-flexible material SFA16 mixed with phase change energy storage material; the lower layer 5 is composed of 8 cm of EME20 high modulus asphalt mixture with a high proportion of RAP, and the base layer 7 is composed of 20 cm of CB-1 cement-stabilized graded crushed stone or gravel mixed with bagasse fiber, waste rubber powder and water-absorbing resin polyacrylate sodium salt. A first adhesive layer 2 is arranged between the surface layer 1 and the middle surface layer 3, and a second adhesive layer 4 is arranged between the middle surface layer 3 and the lower layer 5. The first adhesive layer 2 and the second adhesive layer 4 are SBS modified asphalt adhesive layers or modified emulsified asphalt adhesive layers, and the spreading amount per unit area is 0.7 kg / m 2 The thickness of the rubber asphalt stress absorption layer 6 is 1.3 cm; the base layer 8 is composed of 18 cm assembled regular hexagonal porous cement concrete; a gap 9 is provided along the bottom direction in the lower half of the base layer 8, the distance between adjacent gaps 9 is 1.5 m, and the width of the gap 9 is 2.5 cm.

[0073] In an embodiment of the invention, the semi-flexible material SFA13 is prepared by pouring cement grouting into a rubber asphalt mixture, wherein the void ratio of the rubber asphalt mixture is 28%, and the rubber asphalt mixture is mixed, spread and compacted by the following raw materials in the following weight ratio: aggregate: mineral powder: rubber asphalt = 100:5:5.5; the cement grouting material is prepared by the following raw materials in parts by weight: 30 parts of ordinary Portland cement, 10 parts of grade II fly ash, 15 parts of fine sand, 2 parts of sulfate-based early strength agent, 0.3 parts of polycarboxylic acid water reducer, 6 parts of saponin air entraining agent, 4 parts of carboxylated styrene butadiene latex, 0.4 parts of calcium carbonate, and 35 parts of water.

[0074] The semi-flexible material SFA16 of the phase change energy storage material is prepared by pouring cement grouting material containing phase change energy storage material into rubber asphalt mixture. The design target void ratio of the rubber asphalt mixture is 28%. The rubber asphalt mixture is mixed, spread and compacted by the following raw materials and weight ratio, aggregate: mineral powder: rubber asphalt = 100:5:5.5; the cement grouting material of the phase change energy storage material is prepared by the following raw materials in parts by weight: 50 parts of ordinary Portland cement, 10 parts of grade II fly ash, 10 parts of fine sand, 2 parts of sulfate early strength agent, 0.4 parts of polycarboxylic acid water reducer, 6 parts of sodium carbonate, 0.4 parts of calcium carbonate, 32 parts of water, and 5 parts of phase change energy storage material; emulsified asphalt is wrapped on the outside of the phase change energy storage material, and the phase change energy storage material is prepared by using expanded graphite as an energy storage carrier and one or more of paraffin, fatty acid, and polyethylene glycol as phase change materials, and the mass ratio of the phase change material to the energy storage carrier is 80%. The preparation process of the energy storage carrier (phase change energy storage) material is as follows: placing expanded graphite in an 80°C oven and heating it for 10 hours to ensure that there is no moisture in the expanded graphite; secondly, dissolving polyethylene glycol in 60°C distilled water to prepare a polyethylene glycol aqueous solution; thirdly, mixing the dried expanded graphite with the polyethylene glycol aqueous solution and ultrasonically oscillating at 60°C for 0.8 hours; then placing the expanded graphite and polyethylene glycol mixed solution in an 80°C vacuum drying oven and evacuating it for 6 hours so that the pores of the expanded graphite are filled with polyethylene glycol, thereby obtaining an expanded graphite-polyethylene glycol composite material; finally, slowly adding the expanded graphite-polyethylene glycol composite material to the emulsified asphalt, stirring synchronously and controlling the stirring speed from slow to fast, and when all of them are added, rotating at a constant speed for 0.5 hours, and the stirring speed is 1500 rpm, so that the emulsified asphalt can fully wrap the composite material, thereby preparing a polyethylene glycol phase change energy storage material, and the total mass fraction of the emulsified asphalt and the polyethylene glycol phase change energy storage material is 80%.

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. The road structure of urban intersections, bus stops and bus lanes is characterized by: The road structure comprises a surface layer, a middle layer, a lower layer, a base layer and a subbase layer from top to bottom, wherein a rubber asphalt stress absorption layer is arranged between the lower layer and the base layer, wherein the surface layer is composed of a 4cm~6cm layer of a semi-flexible material SFA13 sprayed with a stone-exposing agent; the middle layer is composed of a 6cm~8cm layer of a semi-flexible material SFA16 mixed with a phase change energy storage material; the lower layer is composed of an 8cm~10cm layer of an EME20 high modulus asphalt mixture with a high proportion of RAP, the base layer is composed of an 18cm~20cm layer of CB-1 cement-stabilized graded crushed stone or gravel mixed with bagasse fiber, waste rubber powder and water-absorbing resin polyacrylic acid sodium salt, and the subbase layer is composed of a 15cm~18cm assembled regular hexagonal porous cement concrete layer; The semi-flexible material SFA13 layer is prepared by pouring cement grouting material into a rubber asphalt mixture, wherein the void ratio of the rubber asphalt mixture is 20% to 28%, and the rubber asphalt mixture is mixed, spread and compacted by the following raw materials in the following weight ratio: aggregate: mineral powder: rubber asphalt = 100: 3 to 5: 3.5 to 5.5; the cement grouting material is prepared by the following raw materials in parts by weight: 30 to 50 parts of ordinary Portland cement, 5 to 10 parts of grade II fly ash, 10 to 15 parts of fine sand, 0.5 to 2 parts of sulfate early strength agent, 0.1 to 0.3 parts of polycarboxylic acid water reducer, 1 to 6 parts of saponin air entraining agent, 1 to 4 parts of carboxylated styrene butadiene latex, 0.1 to 0.4 parts of calcium carbonate, and 15 to 35 parts of water; The semi-flexible material SFA16 layer of the phase change energy storage material is prepared by pouring cement grouting material containing phase change energy storage material into the rubber asphalt mixture. The void ratio of the rubber asphalt mixture is 20%~28%. The rubber asphalt mixture is mixed, spread and compacted by the following raw materials and weight ratios: aggregate: mineral powder: rubber asphalt = 100: 3~5: 3.5~5.5; the cement grouting material of the phase change energy storage material is prepared by the following raw materials in parts by weight: 30~50 parts of ordinary Portland cement, 5~10 parts of grade II fly ash, 5~10 parts of fine sand, 0.5~2 parts of sulfate early strength agent, 0.1~0.3 parts of polycarboxylate water reducer, 1~6 parts of sodium carbonate, 0.1~0.4 parts of calcium carbonate, 12~32 parts of water, and 3~5 parts of phase change energy storage material; Emulsified asphalt is wrapped on the outside of the semi-flexible material SFA16 of the phase change energy storage material. The semi-flexible material SFA16 of the phase change energy storage material is prepared by using expanded graphite as an energy storage carrier and one or more of paraffin, fatty acid, and polyethylene glycol as phase change materials. The mass ratio of the phase change material to the energy storage carrier is 40%-80%.

2. The road structure of the urban intersection, bus station and bus lane according to claim 1, characterized in that: A first adhesive layer is arranged between the surface layer and the middle surface layer, and a second adhesive layer is arranged between the middle surface layer and the lower layer. The first adhesive layer and the second adhesive layer are SBS modified asphalt adhesive layers or modified emulsified asphalt adhesive layers, and the spreading amount per unit area is 0.7-0.8 kg / m 2 .

3. The road structure of the urban intersection, bus station and bus lane according to claim 1, characterized in that: The thickness of the rubber asphalt stress absorption layer is 0.8 cm to 1.3 cm.

4. The road structure for urban intersections, bus stops and bus lanes according to claim 1, characterized in that: The lower half of the base layer is provided with gaps along the bottom direction, the distance between adjacent gaps is 0.6m-1.5m, and the width of the gaps is 0.5cm-2.5cm.

5. The road structure for urban intersections, bus stops and bus lanes according to claim 1, characterized in that: The EME20 high modulus asphalt mixture layer with a high proportion of RAP is formed by mixing, paving and compacting raw materials in the following weight ratio: aggregate: mineral powder: low-grade road asphalt = 100: 5~6: 5.5~6.5, wherein the aggregate contains 25~50% of RAP old materials.

6. The road structure for urban intersections, bus stops and bus lanes according to claim 1, characterized in that: The base layer is formed by mixing, spreading and compacting bagasse fiber, waste rubber powder and CB-1 cement-stabilized graded crushed stone or gravel containing water-absorbing resin polyacrylic acid sodium salt. The base layer is formed by mixing, spreading and compacting raw materials in the following weight ratio: aggregate: ordinary Portland cement: bagasse fiber: waste rubber powder: water-absorbing resin polyacrylic acid sodium salt = 100: 4~6.5: 0.3~0.8: 0.5~3.5: 0.1~0.

3.

7. The road structure of the urban intersection, bus station and bus lane according to claim 1, characterized in that: The 15-18 cm assembled regular hexagonal porous cement concrete layer has a strength grade of not less than C20 and a porosity of 10%-15%. The assembled regular hexagonal porous cement concrete layer is made by mixing the following raw materials: 5 mm-10 mm coarse aggregate 1629 kg / m 3 , cement 503 kg / m 3 , water 150.9 kg / m 3 , water reducing agent 2.0kg / m 3 、Rubber powder 15.1kg / m 3 and polyvinyl alcohol powder 4.0kg / m 3 ; Wherein, the coarse aggregate is made of natural coarse aggregate 814.5~1140.3kg / m 3 and recycled coarse aggregate 488.7~814.5kg / m 3 composition.

Citation Information

Patent Citations

  • Semi-flexible composite road surface structure and building method thereof

    CN101096837A

  • Semi-flexible heavy-duty pavement paving structure

    CN103866667A

  • Semi-flexible composite pavement structure and preparation method thereof

    CN105481322A

  • Semi-flexible pavement material, preparation method therefor and semi-flexible pavement

    CN106587842A

  • Half flexible bituminous paving basic unit structure

    CN205134126U